ANALYSIS OF VEGETABLE FARMING INCOME AND ITS CONTRIBUTION TO FAMILY INCOME IN GEMPOL VILLAGE, PEJATEN VILLAGE, KRAMATWATU DISTRICT, SERANG REGENCY - Azka Khaerunnisa; Aris Supriyo Wibowo; Mirajiani; Dian Anggraeni (RADJA PUBLIKA, 2026)
This study aims to analyze vegetable farming income and its contribution to household income in Gempol Hamlet, Pejaten Village, Kramatwatu Subdistrict, Serang Regency. The background of this study is based on the shift from rice to vegetable cultivation, which has a shorter growing cycle and the potential to increase household cash flow. The research method employs a quantitative approach with data collection through interviews, observations, and documentation. The results indicate that vegetable farming makes a significant contribution to household income, despite facing relatively high production costs and market price fluctuations. Family support for vegetable farming is also evident in social, economic, and educational aspects. The policy implications of this study highlight the need for local government support in the form of providing production facilities, more stable market access, and farmer empowerment programs to enhance the efficiency and competitiveness of vegetable farming. Thus, vegetable farming not only plays a role in improving the well-being of farming households but also supports rural economic development.